Prenatal Diagnosis of Twin Fetuses with a Novel AR Gene Mutation in a Chinese Family of Complete Androgen Insensitivity Syndrome. (2nd November 2017) - Wu, Weiqing; Geng, Qian; Liu, Yang; Xu, Zhiyong; Li, Peining; Xie, Jiansheng
ABSTRACT: Introduction and aims : Androgen insensitivity syndrome (AIS) is an X-linked recessive genetic disorder caused by mutations in the androgen receptor (AR) gene. Only a few cases of AIS with AR gene mutations have been diagnosed prenatally. This study aimed to investigate the gene mutation in a Chinese complete androgen insensitivity syndrome family and perform prenatal diagnosis for twin fetuses. Case report : We evaluated the AR gene of the child proband in a Chinese CAIS family, and detected a novel mutation c.3864T>C (p. Phe917Leu). Amniocentesis was performed when the mother presented to our hospital with a subsequent twin pregnancy. Mutation analysis revealed that both fetuses were hemizygous for this mutation. The aborted fetuses had typical female external genitalia and bilateral testes in abdomen. Conclusion : The c.3864T>C AR novel mutation is responsible for complete androgen insensitivity syndrome, and its identification was subsequently used for a subsequent successful prenatal diagnosis.